Harmonization of The Role of Religious and State Justice Institutions in Handling Victims of Domestic Violence - Ismiati, Saptosih; Widjanarto, Haswar; Wafa Azizah, Ersya Aqila (Ann Publisher, 2024)
Domestic abuse is a subject of public law, thereby transcending the private sphere of the marital relationship and necessitating official intervention in its resolution. Domestic violence falls under criminal law, although divorce pertains to civil family law, resulting in two distinct legal processes in the divorce settlement that follow incidents of domestic abuse. Law Number 23 of 2004 addresses the Elimination of Domestic Violence, serving as the inaugural legislative framework that explicitly safeguards victims of domestic violence offenses. This study employs a descriptive-analytical research methodology. This study employs a normative juridical approach, utilizing literature and secondary data as the foundation for research, which involves an examination of relevant laws, regulations, and literature pertinent to the research process. Simultaneously, the analysis employed in this study methodology is qualitative legal. This study concluded that the Religious Court lacks the authority to adjudicate domestic violence cases, as it does not possess jurisdiction over public law matters. In addressing community needs, the majority of domestic violence cases are promptly adjudicated for divorce in the Religious Court without prior resolution in the District Court. Consequently, harmonization between the Religious Court and the District Court is necessary for the resolution and adjudication of divorce cases involving domestic abuse. Immediate formulation of clear and tangible regulations is necessary to address divorce cases stemming from domestic abuse, namely by granting the Religious Court the competence to adjudicate matters pertaining to public law, particularly those involving domestic violence.